Morphology of TiAlN Thin Film onto HSS as Cutting Tools by Using Mosaic-Styled Target RF Sputtering Method - Sigit Tri Wicaksono; Agung Purniawan; I.G.N.B Dwistha Prayukti; Tri Mardji Atmono (Chemistry Department, The University of Brawijaya, 2016)
High Speed Steel (HSS) has been widely used in manufacturing industry as cutting tools. Several methods have been used to improve the cutting performance of HSS in dry cutting. One of them was by growing a thin layer of hard coating on the contact surface of the cutting tool material. In this research, Titanium Aluminum Nitride (TiAlN) layer were deposited on AISI M41 HSS substrate by using Radio Frequency (RF) sputtering method with mosaic styled of target materials. The aluminum surface area ratios on the Titanium target are 10, 20, 30, and 40 % respectively. The deposition time are 15, 30, and 45 minutes respectively. The formation of TiAlN and AlN crystalline compounds were observed by X-Ray Diffraction method. The morphology of thin film layer with a thickness range from 1.4 to 5.2 µm was observed by using a Scanning Electron Microscopy. It was known that the deposition time affect to the thickness and also the roughness of the layer. The topography images by Atomic Force Microscopy showed that the deposition time of 45 minutes produce the finest layer with the surface roughness of 10.8 nm.